The Iraqi Federal Court's cancellation of the Khor Abdullah Agreement with Kuwait and its impact on future relations between the two countries - Hamid Jabr, Lect . Dr. Hazim (Basra studies journal, 2025)
This study examines the decision of the Iraqi Federal Supreme Court to annul the Khor Abdullah Agreement signed with Kuwait and analyzes the impact of this ruling on the future of bilateral relations between the two countries. It reviews the background and context of the agreement, as well as the legal and political justifications cited by the court in its decision. The study also discusses regional and international reactions, particularly those from the Gulf Cooperation Council (GCC) states, and explores possible scenarios for Iraqi-Kuwaiti relations ranging from escalation to reconciliation. It concludes that the annulment reflects the complexities of maritime sovereignty and may reignite tensions unless addressed through dialogue and diplomacy.